2012
DOI: 10.1111/j.1574-6976.2011.00285.x
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of secondarymetabolism and development in fungi: the velvet familyof regulatory proteins

Abstract: Filamentous fungi produce a number of small bioactive molecules as part of their secondary metabolism ranging from benign antibiotics such as penicillin to threatening mycotoxins such as aflatoxin. Secondary metabolism can be linked to fungal developmental programs in response to various abiotic or biotic external triggers. The velvet family of regulatory proteins plays a key role in coordinating secondary metabolism and differentiation processes such as asexual or sexual sporulation and sclerotia or fruiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
500
3
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 490 publications
(537 citation statements)
references
References 179 publications
13
500
3
5
Order By: Relevance
“…Light is sensed by photoreceptors that transmit the signal to recipients like the velvet regulators. In the dark, the velvet protein VeA is transported together with the second velvet-like protein VelB into the nucleus, where they can form together with the putative methyltransferase LaeA the trimeric VelB-VeA-LaeA complex which coordinates sexual development and secondary metabolism (Bayram and Braus, 2011;Bayram et al, 2008). A. nidulans LaeA is required for secondary metabolite expression of the sterigmatocystin (ST) or penicillin clusters (Bok and Keller, 2004;Bok et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Light is sensed by photoreceptors that transmit the signal to recipients like the velvet regulators. In the dark, the velvet protein VeA is transported together with the second velvet-like protein VelB into the nucleus, where they can form together with the putative methyltransferase LaeA the trimeric VelB-VeA-LaeA complex which coordinates sexual development and secondary metabolism (Bayram and Braus, 2011;Bayram et al, 2008). A. nidulans LaeA is required for secondary metabolite expression of the sterigmatocystin (ST) or penicillin clusters (Bok and Keller, 2004;Bok et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…We found that both RsmA and NapA, previously identified as having a major role in the fungal stress response, have significant and distinct effects on SM and sexual development, a linkage previously characterized by the Velvet Complex (Bayram & Braus, 2012).…”
Section: Introductionmentioning
confidence: 93%
“…In addition to the specific TFs, putative global regulators that are involved in the regulation of more diverse functions have also received attention. Recently, the velvet family proteins, which are global regulators conserved in filamentous fungi (Bayram & Braus, 2012;Jiang et al, 2011;Kato et al, 2003;Kim et al, 2002;Merhej et al, 2012;Wiemann et al, 2010), have been identified in F. graminearum. In Aspergillus nidulans, the velvet protein complex forms a heterotrimeric complex consisting of VelB-VeA-LaeA proteins, and regulates diverse cellular functions such as sexual development and secondary metabolism by participating in chromatin remodelling.…”
Section: Introductionmentioning
confidence: 99%